Role of personality traits in determining the association between social participation and mental health: A cross-sectional study in Japan. (January 2023) - Yamashita, Mari; Abe, Takumi; Seino, Satoshi; Nofuji, Yu; Sugawara, Yasuhiro; Shinkai, Shoji; Kitamura, Akihiko; Fujiwara, Yoshinori
The role of personality in determining the association between social participation and mental health was examined by a cross-sectional study. We analyzed data from 4981 older adults aged 65–84 years who were recruited via a mail survey in one region of Japan. We defined poor mental health using a score ≤12 points on the World Health Organization-Five Well-Being Index-Japanese. Personality traits were measured by 10 Item Personality Inventory-Japanese. In women, higher openness positively moderated the association between private group participation (volunteering, sports, hobby, and learning) and mental health, while higher neuroticism negatively moderated it. This study contributes to knowledge about mental health, personality, and participation. The findings provide provisional evidence about recommending private group participation for women with high openness but not those with high neuroticism.